ANALISIS PENGARUH INFLASI, NILAI TUKAR, ROA, DER DAN CR TERHADAP RETURN SAHAM - Diana Kurniawati (Gapenas Publisher, 2025)
The growth of the Indonesian capital market is an important indicator of the national economy, forming the need to understand the factors that suggest stock returns. This study aims to analyze the effect of inflation, exchange rate, Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on the return of shares of companies listed on the Indonesia Impact Exchange. The quantitative approach was applied using a correlational research design, utilizing secondary data from the company's financial statements and official macroeconomic data for the 2019–2023 period. The analysis method used includes multiple linear regression, accompanied by classical assumption testing to ensure the validity of the model. What will happen is that inflation and exchange rates have a negative and significant impact on stock returns, while ROA has a significant positive effect. on the other hand, DER and CR do not have a significant impact on stock returns. These findings confirm that external macroeconomic variables have a significant impact on stock performance. So far, among the internal financial indicators, the company's profitability has become the most dominated factor. The contribution of this research lies in a more comprehensive understanding of the simultaneous impact of internal and external factors on stock returns in the Indonesian capital market, as well as providing simple implications for investors and financial managers in designing investment strategies that are more adaptive to economic changes.